Impacts of Extracts From Styrax officinalis L. on Seedling Growth of Salvia sclarea L. - Belgin COŞGE ŞENKAL; Tansu USKUTOĞLU (ISPEC Journal of Agricultural Sciences)
Many plant species synthesize different biochemical substances from their various organs (leaves, flowers, fruits and roots, etc.). While some of these biochemical substances which are known as allelochemicals have a stimulating effect on the growth and development of other plants, some of them have an inhibitory effect. In this study, the effect of extracts obtained from the Styrax officinalis L., which spreads naturally in the Mediterranean and Aegean regions, on the seedling growth of Salvia sclarea L. were investigated. In the study, the extracts prepared with water at 5% concentration from dry fruit peel and seed coat of S. officinalis, and tap water as control were used. According to the results of this study, it was determined that the fruit peel and seed coat extracts obtained from S. officinalis had a significant inhibitory effect on the emergence of S. sclarea seeds and its seedling growth. The inhibitory effect of fruit peel was higher than that of seed coat.